PENATAAN KELEMBAGAAN PENYELENGGARA PEMILU DAN PILKADA DALAM MENINGKATKAN INTEGRITAS DEMOKRASI DI INDONESIA - Wahyu Hindiawati; Ismawati Ismawati; Abdul Haq; Amelia Ayu Paramitha; Hezron Sabar Rotua Tinambunan (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
Following the rise of issues like overlapping authority, regulatory inconsistency, inter-institutional contestation, and low public trust in election results, the institutional arrangement of election and regional head elections (Pilkada) organizers is a crucial component in bolstering the integrity of Indonesia's democracy. To guarantee the General Election Commission (KPU), the Election Supervisory Body (Bawaslu), and the Election Organizer Honorary Council (DKPP) can perform their duties competently and honestly, a thorough assessment of their institutional design is required under these circumstances. Finding a model of arrangement that may enhance the quality of procedural and substantive democracy is the urgent goal of this research, which also intends to assess the urgency of institutional arrangement of election and regional head elections (Pilkada) organizers. By reviewing statutes, case law, academic publications, and election administration practices throughout many election cycles, this study employs a normative legal research methodology that is conceptual, comparative, and based on statutes. The study shows that regulatory disharmony, unclear authority boundaries, overlapping conflict resolution systems, and insufficient election organizing institution coordination are the key issues. Independence, professionalism, accountability, and openness in elections also affect institutional integrity. The study finds that election and regional election organizers must align legislation, reinforce organized authority, build institutional capacity, and improve coordinating mechanisms to safeguard Indonesian democracy. Keywords: Institutional Arrangement, Elections, Regional Head Elections, Democratic Integrity.